2015
DOI: 10.1093/nar/gkv1104
|View full text |Cite
|
Sign up to set email alerts
|

BioGPS: building your own mash-up of gene annotations and expression profiles

Abstract: BioGPS (http://biogps.org) is a centralized gene-annotation portal that enables researchers to access distributed gene annotation resources. This article focuses on the updates to BioGPS since our last paper (2013 database issue). The unique features of BioGPS, compared to those of other gene portals, are its community extensibility and user customizability. Users contribute the gene-specific resources accessible from BioGPS (‘plugins’), which helps ensure that the resource collection is always up-to-date and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
348
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(366 citation statements)
references
References 12 publications
16
348
0
2
Order By: Relevance
“…Data were retrieved from the integrated data set of human gene expression patterns (http://biogps.org/). 17 Expression was measured using the U133 Affymetrix chip; *MALAT1 abundance is expressed as gcrma‐normalized expression data relative to fluorescence intensity. Grna: Because there are multiple probes for each transcript on the microarray, the intensity values were summarized using various data processing algorithms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were retrieved from the integrated data set of human gene expression patterns (http://biogps.org/). 17 Expression was measured using the U133 Affymetrix chip; *MALAT1 abundance is expressed as gcrma‐normalized expression data relative to fluorescence intensity. Grna: Because there are multiple probes for each transcript on the microarray, the intensity values were summarized using various data processing algorithms.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we retrieved gene expression data pertaining to MALAT1 abundance in inflammatory response‐related cells from the integrated data set of human gene expression patterns (BioGPS) 17. The analysis indicated that MALAT1 is highly expressed in a large number of immune‐related cells, including lymphocyte and leukocyte subsets, although the relative abundance seems to be different in B and T cells, with higher levels of expression noted in the latter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To completely rule out such contamination, analyses based on single isolated adipocytes would seem to be required. We used available published data and BioGPS 37 (http://biogps.org) to examine to what extent the genes exhibiting concurrent changes in DNA methylation and expression represented genes expressed in mature adipocyte. This survey showed that all these genes with the exception of Arhgap6 are reported to be expressed in mature adipocytes, but also showed that Irf8, Prcp, Setd6, Shank3, Nrp2 Zfp521, Pkig, and Cpt1a are expressed in cell of the stromal vascular fraction that may contaminate the mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…All these proteins are known to be expressed in the colorectal epithelium (28-33), but to date there is no reported evidence of their glycoprotein nature. Therefore, even though some of the proteins have been associated with CRC and other types of neoplasia, including keratin 19 (28), LRMP (29), RPSA (30), GRP-78 (31) and ERp44 (33), these proteins were not further analyzed in subsequent studies. The ATP synthase subunit β (34) and the cytochrome b-c1 complex subunit 1 (35) are mitochondrial proteins associated with ATP production.…”
Section: Discussionmentioning
confidence: 99%